2023
DOI: 10.3390/antibiotics12020293
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of an Azithromycin-Colistin Combination against XDR K. pneumoniae in a 3D Collagen-Based In Vitro Wound Model of a Biofilm Infection

Abstract: A therapeutic combination of azithromycin (AZM) and colistin methanesulfonate (CMS) was shown to be effective against both non-PDR and PDR Klebsiella pneumoniae biofilms in vitro. These anti-biofilm effects, however, may not correlate with effects observed in standard plate assays, nor will they representative of in vivo therapeutic action. After all, biofilm-associated infection processes are also impacted by the presence of wound bed components, such as host cells or wound fluids, which can all affect the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Until transportation to Kyiv City Clinical Hospital No 6 and within the first 8 days, only MDR gram-negative isolates were detected. It is important to emphasize that all these four isolates were sensitive to tigecycline, and they hypothetically may be still sensitive to colistin, as colistin-resistance is still not so often encountered in Ukrainian hospital isolates, as demonstrated before (16) or as demonstrated by other authors (17). However, despite this rational combined antimicrobial therapy with colistin and tigecycline, the condition of the patient decreased: he had hypothermia, anemia, underwent two blood transfusions, his bilirubin level was increased and PCT varied from 3.247 to 1.698 ng/mL (Figure 3).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Until transportation to Kyiv City Clinical Hospital No 6 and within the first 8 days, only MDR gram-negative isolates were detected. It is important to emphasize that all these four isolates were sensitive to tigecycline, and they hypothetically may be still sensitive to colistin, as colistin-resistance is still not so often encountered in Ukrainian hospital isolates, as demonstrated before (16) or as demonstrated by other authors (17). However, despite this rational combined antimicrobial therapy with colistin and tigecycline, the condition of the patient decreased: he had hypothermia, anemia, underwent two blood transfusions, his bilirubin level was increased and PCT varied from 3.247 to 1.698 ng/mL (Figure 3).…”
Section: Discussionmentioning
confidence: 58%
“…The newly suggested therapy was focused on anti-biofilm therapy and included azithromycin which was effective against gram-negative XDR/PDR Ukrainian Hospital Isolates as shown before ( 16 , 18 ). The combination therapy with azithromycin and meropenem was suggested based on own previous experimental and clinical data which confirmed that both antibiotics demonstrated a strong synergistic effect in vivo against diverse gram-negative hospital isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, we used the porous 3D collagen scaffolds, developed using freezedrying technique described in our previous study [8]. The technique allowed obtaining the scaffolds that had an average pore diameter of 117±57 µm.…”
Section: Resultsmentioning
confidence: 99%
“…Collagen scaffold preparation. The porous collagen scaffolds were produced from a solution of bovine atelocollagen in acetic acid using a freeze-drying technique described previously [8]. Briefly, the solution of type I atelo collagen, isolated from a bovine tendon, of 20 mg/mL in 0.5 M acetic acid was prepared.…”
Section: Methodsmentioning
confidence: 99%
“…The combination of 8 µg/mL SPR741, 16 µg/mL clarithromycin, and 16 µg/mL erythromycin was found to be the most potent against pre-formed biofilms (48 hours). Moshynets et al investigated the therapeutic potential of AZM-CMS combination against XDR K. pneumoniae isolates using 3D Collagen-Based in vitro wound model of biofilm infection, and the results confirmed AZM to be an effective antibiofilm drug used either alone or in combination with CMS (Moshynets et al, 2023).…”
Section: Combination Of Antibioticsmentioning
confidence: 97%